State immunological reactivity and autonomic regulation in patients with chronic apical periodontitis (LLC "Endo Press", 2020)
Chronic apical periodontitis due to exceptionally high prevalence is one of the first places as a source of focal-related diseases. Teeth with destructive periodontal remain potentially dangerous foci of infections caused by autonomic imbalance and immune status. In this paper we studied 107 people with a diagnosis of «chronic apical periodontitis». The functional state of the autonomic nervous system were detected by electrophoresis dosed adrenaline and carbachol and test dermographism. To evaluate the immune used to determine the number of leukocytes and blood leukocyte, a T-lymphocyte, B-lymphocytes, theophylline-resistant lymphocytes, phagocytic index and phagocytic number of serum immunoglobulins. The necessity of restoring the physiological level of functioning of the nervous system in terms of its excitability threshold, the severity of the reactions and the ratio of sympathetic and parasympathetic divisions.